Development of Google Sites-Based Career Card Media for Career Understanding at Junior High School 3 Palangka Raya - Cahyono, Hadi; Suriatie, Mimi; Sendayu, Fendahapsari Singgih; Feronika, Nopi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Career understanding is a person's understanding of career information, which can be in the form of jobs matching their interests, talents, and abilities needed to carry out the job. However, some students have a low level of career understanding, so many are confused when choosing a secondary school without consideration. With this Google Sites-based career card media, students can better understand secondary schools and various types of careers. This study was conducted to determine the feasibility of Google Sites-based career card media and to find out whether this Google Sites-based career card media is useful for students' career understanding. This study uses a Research and Development (R&D) approach, namely research and development, and produces a product, namely a career card and a Google Sites-based career card media for career understanding. The development model was adapted from Borg and Gall and included six stages of development research. The sample was taken using the purposive sampling technique, so six students from class VIII-2 of Junior High School 3 Palangka Raya were selected. The main data collection tool used by researchers is a questionnaire. Researchers use a questionnaire to determine whether there are changes before and after using Google Sites-based career card media for career understanding. The data was then analyzed and processed using parametric statistics from Kolmogorov-Smirnov using SPSS 26, which showed a normal distribution. The results showed that the t-test calculation using the paired sample t-test showed a significance of 0.000 < 0.05, and the calculated t-value compared to the t-table value was 24.265 > 2.015. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that there is a significant difference between before and after using Google Sites-based career card media for career understanding.